2020
DOI: 10.1093/rheumatology/keaa378
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of persistent inflammation in familial Mediterranean fever and association with damage

Abstract: Objective Persistent inflammation is an insidious and less studied feature of FMF. We investigated clinical determinants of persistent inflammation and its associations with individual damage items. Methods This is a cross-sectional analysis of 917 FMF patients, who fulfilled the Tel Hashomer criteria and had at least 6 months’ follow-up. Patients were stratified based on whether they had persistent inflammation. We used logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
1
13
0
2
Order By: Relevance
“…However, subclinical chronic inflammation continues during the attack-free period [21][22][23][24]. In our study, comparison of attack-free patients with the healthy control group revealed that CRP, S100A12, and ESR levels were significantly higher in attack-free patients than in the control group.…”
Section: Discussionmentioning
confidence: 42%
“…However, subclinical chronic inflammation continues during the attack-free period [21][22][23][24]. In our study, comparison of attack-free patients with the healthy control group revealed that CRP, S100A12, and ESR levels were significantly higher in attack-free patients than in the control group.…”
Section: Discussionmentioning
confidence: 42%
“…In a recent study by Babaoglu et al conducted with 917 FMF patients, the age of onset of the patients whose in ammation continued even during the attack free period was shown to present earlier; they were exposed to more frequent attacks of arthritis. It was found that this condition increased the development of amyloidosis by 3.59 fold, proteinuria development 3.28 fold, and kidney failure 4.18 fold (19). In addition, in early disease onset FMF patients, the international Severity of Scoring System (ISSF) was observed to be higher in FMF (25).…”
Section: Discussionmentioning
confidence: 96%
“…The presence of subclinical in ammation triggers many complications such as growth failure, puberty delay, and osteoporosis (19).…”
Section: Discussionmentioning
confidence: 99%
“…The extent of renal damage defines the patients' prognosis, and renal biopsy is the most common diagnostic test revealing amyloid deposits. The majority of reports on FMF-related AA amyloidosis are retrospective in nature or case series [2][3][4][5][6][7]. The pathogenesis and risk factors for amyloidosis in FMF remain partially understood.…”
Section: Introductionmentioning
confidence: 99%